PENGARUH PROFITABILITAS, SOLVABILITAS, DAN LIKUIDITAS TERHADAP RETURN SAHAM : SURVEI PADA PERUSAHAAN CONSUMER GOODS YANG TERDAFTAR DI BURSA EFEK INDONESIA - Rahmawati, An Nisa’; Lestari, Sri Isfantin Puji; Sukamdiani, MG (Jurnal Revenue : Jurnal Ilmiah Akuntansi, 2025)
The aim of this research is to determine the influence of profitability, solvency and liquidity partially and simultaneously on stock returns. In this research, the sampling technique is purposive sampling technique, which means sampling is based on certain criteria. The data analysis techniques used are the Classic Assumption Test, Multiple Linear Regression Test, t Test and F Test. The research results show that the profitability and liquidity variables partially have a negative and insignificant effect on stock returns. Meanwhile, the solvency variable partially has a positive and significant effect on stock returns. Simultaneously, these three variables (profitability, solvency and liquidity) have a positive and significant effect on stock returns